Determination of Economic Climate Change and Development of the Internet of Things: Analysis of Business Sustainability and Competitive Advantage - Agus Dharmanto; Tri Widyastuti; Ni Nyoman Sawitri; Ningki Sasanti (Greenation International Journal of Economics and Accounting, 2024)
Purpose – The goal of this work is to construct a hypothesis on the influence of factors that may subsequently be used for further research within the area of marketing management. Design/methodology/approach – The research method chosen was descriptive qualitative. Data was acquired from past research that is relevant to this study and sourced from academic internet media such as Publish or Perish, Google Scholar, digital reference books, and the journal Sinta. Findings – The findings of this study show that: 1) Climate change affects business sustainability; 2) The development of the internet of things has an impact on business continuity; 3) Climate change affects competitive advantage; 4) The development of the internet of things influences competitive advantage; and 5) Business sustainability influences competitive advantage. Research limitations/implications – The constraints of the data used in this study mean that the results produced are less than perfect. Practical implications – This research is valuable for business executives who want to understand the influence of climate change and the expansion of the Internet of Things on their company's sustainability and competitive advantage.